2018
DOI: 10.1126/science.aau2093
|View full text |Cite
|
Sign up to set email alerts
|

Swifter, higher, stronger: What’s on the menu?

Abstract: The exploits of elite athletes delight, frustrate, and confound us as they strive to reach their physiological, psychological, and biomechanical limits. We dissect nutritional approaches to optimal performance, showcasing the contribution of modern sports science to gold medals and world titles. Despite an enduring belief in a single, superior “athletic diet,” diversity in sports nutrition practices among successful athletes arises from the specificity of the metabolic demands of different sports and the perio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
95
1
3

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 90 publications
(100 citation statements)
references
References 95 publications
1
95
1
3
Order By: Relevance
“…Physiological responses to exercise performed within moderate-(<LT), heavy-(>LT but <CS), and severe (>CS)intensity domains differ considerably (Poole et al, 2016) with implications for the predominant cause(s) of fatigue (Black et al, 2017). The goal of race nutrition is to address the factors that would otherwise cause fatigue or suboptimal outputs during and especially toward the end of an event (Burke & Hawley, 2018). Table 1 indicates that substrate availability for the muscle (glycogen and glucose) and brain (glucose) is a key issue for many distance events, along with the offset of sweat loss to preserve plasma volume and cardiac output.…”
mentioning
confidence: 99%
“…Physiological responses to exercise performed within moderate-(<LT), heavy-(>LT but <CS), and severe (>CS)intensity domains differ considerably (Poole et al, 2016) with implications for the predominant cause(s) of fatigue (Black et al, 2017). The goal of race nutrition is to address the factors that would otherwise cause fatigue or suboptimal outputs during and especially toward the end of an event (Burke & Hawley, 2018). Table 1 indicates that substrate availability for the muscle (glycogen and glucose) and brain (glucose) is a key issue for many distance events, along with the offset of sweat loss to preserve plasma volume and cardiac output.…”
mentioning
confidence: 99%
“…At the molecular level, exercise with reduced CHO availability enhances expression and/or activity of proteins involved in oxidative metabolism of fatty acids (FAs) and mitochondrial biogenesis in skeletal muscle. 3,15,16 Evidence suggests that the molecular mechanism for this involves activation of AMP-activated protein kinase (AMPK) and the downstream transcription factor, peroxisome proliferator-activated receptor γ coactivator 1α (PGC-1α). [17][18][19] While mitochondrial adaptations have been investigated extensively, intramuscular lipolysis has not received similar attention.…”
mentioning
confidence: 99%
“…We also showed that net skeletal muscle glycogen utilization and acute skeletal muscle mRNA responses were largely unaffected by the same exercise performed before versus after breakfast. This is important, because muscle glycogen availability can alter muscle adaptations to training (27). Lower muscle glycogen concentrations are therefore unlikely to have driven the training responses we observed in the training study with the present method of nutrient-exercise timing.…”
Section: Discussionmentioning
confidence: 99%
“…Emerging data in lean, healthy men suggests that nutrient provision affects adaptive responses to exercise training (26, 27). However, feeding and fasting may exert different physiological responses in people who are overweight or obese compared to lean individuals, for example, extended morning fasting versus daily breakfast consumption upregulates the expression of genes involved in lipid turnover in adipose tissue in lean, but not in obese humans (28).…”
Section: Introductionmentioning
confidence: 99%